Ichthyodiversity of a small coastal river in Bangladesh (Dhaka University Journal of Biological Sciences, 2023)
Small rivers are often ignored in terms of conservation actions and biodiversity management in Bangladesh. Despite having significant ecological and economic importance of these rivers, there is limited study done so far. To partially fulfill this gap, this study aimed to assess the fish and shellfish biodiversity of a small coastal river named Tiakhali from southern Bangladesh. A total of 26 finfish and 7 shellfish species were identified where 50% of finfish and all of the shellfish species were from the order Perciformes and Decapoda, respectively. Results showed that 76.9% of finfish and all of the shellfish species were categorized into the least concern category based on IUCN Red List. Estimated Shannon’s, Margalef’s, Buzas & Gibson’s and Simpson’s indices were 1.189, 2.649, 0.435 and 0.435 for fish and 1.662, 0.758, 0.224 and 0.224 for shellfish, respectively. This study showed that Tiakhali river’s fish biodiversity was comparatively smaller than big rivers. The findings of this study might serve as a baseline for future works and will help policymakers to pay attention to conserve such small rivers and their biodiversity in future.Dhaka Univ. J. Biol. Sci. 32(1): 1- 10, 2023 (January)